1998
DOI: 10.1097/00006250-199810001-00004
|View full text |Cite
|
Sign up to set email alerts
|

Hydropic Degenerating Leiomyoma Presenting as Pseudo-Meigs Syndrome With Elevated Ca 125

Abstract: Background: Leiomyomas rarely cause pseudo-Meigs syndrome. Increased levels of CA 125 often are associated with some types of malignancy. No reported case of pseudoMeigs syndrome presenting with hydropic degeneration of uterine leiomyoma and an elevated CA 125 level could be found on a MEDLINE search. Case: A 46-year-old woman presented with a pleural effusion and a pelvic mass measuring 30 ؋ ؋ ؋ 18 cm. Preoperative evaluation was remarkable for a CA 125 level of 254 U/mL. At laparotomy, the diagnosis was a be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 5 publications
1
17
0
4
Order By: Relevance
“…These benign tumours include those of the fallopian tube or uterus or mature teratomas,struma ovarii or ovarian leiomyomas. 4 Surgical treatment includes unilateral salpingooophorectomy to total hysterectomy with b/l salpingooophorectomy depending upon age and parity of the patient and whether the tumour is u/l or b/l.…”
Section: Discussionmentioning
confidence: 99%
“…These benign tumours include those of the fallopian tube or uterus or mature teratomas,struma ovarii or ovarian leiomyomas. 4 Surgical treatment includes unilateral salpingooophorectomy to total hysterectomy with b/l salpingooophorectomy depending upon age and parity of the patient and whether the tumour is u/l or b/l.…”
Section: Discussionmentioning
confidence: 99%
“…This syndrome is an important consideration in the differential diagnosis of ovarian cancer, and rarely causes fatal manifestations . Only 32 studies on pseudo‐Meigs' syndrome complicated with uterine leiomyoma have been reported using a medline search (search terms: pseudo‐Meigs' and leiomyoma, leiomyoma and ascites) since 1900 (Table ) . The association of uterine leiomyoma with ascites and/or PE was first reviewed by Kelly and Cullen in 1909 .…”
Section: Discussionmentioning
confidence: 99%
“…Meigs syndrome was first defined by J. V. Meigs (4,5). Pseudo-Meigs syndrome consists of pleural effusion, ascites, and a benign tumor of the ovary other than fibromas (6). Ascites and hydrothorax should be a collection of malignant fluid.…”
Section: Discussionmentioning
confidence: 99%